47.1: Invited Paper: Practical Application of TI DLP® Technology in the Next Generation Head‐up Display System. Issue 1 (June 2015) - Pettitt, Greg; Ferri, John; Thompson, Jason
Abstract : Next generation automotive head‐up display (HUD) could fundamentally change how OEMs utilize a HUD. A significantly larger virtual display area and vastly improved image quality are two of the many benefits. Along with the benefits come a unique set of challenges, which can be addressed by incorporating TI DLP ® product solutions. This paper explores options for these challenges, including a comparison of different solid state illumination sources, and offers practical solutions for developers.